Implementation of National Tourism Strategic Area Policy in the Seribu Islands: Towards a Collaborative Governance Model - Hastuti, Puji; Effendy, Khasan; Maryani, Dedeh; Sartika, Ika (Ilomata International Journal of Management, 2026)
This study examines the implementation of the National Tourism Strategic Area (KSPN) policy in the Seribu Islands Administrative Regency, Indonesia, focusing on multi-level governance challenges and unequal distribution of tourism benefits in archipelagic regions. Existing studies have largely emphasized planning and economic impacts, with limited attention to policy implementation dynamics in contexts of overlapping institutional authorities. Using a qualitative approach within a post-positivist paradigm, data were collected through in-depth interviews, observations, and document analysis involving 28 informants. Analysis employed the Miles and Huberman interactive model with theoretical triangulation based on Grindle’s policy implementation framework and collaborative governance perspectives. Findings reveal that implementation effectiveness is shaped by policy content and implementation context. The policy contributed to a 1.7% increase in tourist visits in 2024 and stimulated local micro and small tourism enterprises. However, structural challenges persist, including regulatory fragmentation, unequal access to tourism opportunities, and limited inter-institutional coordination. The study proposes a collaborative governance model integrating multilevel coordination, community participation, and sustainable tourism principles as an adaptive framework for archipelagic regions. This research contributes to the literature by offering a context-specific model of tourism policy implementation in archipelagic governance systems and provides recommendations for improving sustainable tourism development in Indonesia’s National Tourism Strategic Areas.